Determinação de rigidez torcional de mola aplicada em cambio cvt de protótipo baja - Guerra, Lucas de Sousa Gurgel (Universidade Federal Rural do Semi-Árido, 2018)
Baja's off-road vehicle development projects offer a very interesting opportunity and student conceptions grow parallel to the mastery level of the characteristics of all vehicle subsystems. These vehicles use CVT gears, which continuously transfer the engine power, with infinite gears ratio. The CVT model used in the CT-18 prototype of the Baja project developed at the UFERSA campus in the city of Caraúbas is the Comet 780, widely used in projects spread throughout Brazil. The present work has as general objective to characterize the torsional constant of the springs applied in the exchange, in order to increase the range of opportunities of manipulation of the performance of the vehicle, benefiting the team. The study is based on the application of the knowledge of machine elements in determining the torsional constant of the springs. With the physical analysis of the same, survey of its characteristics and constructive parameters. Then, an analytical method was used to determine stiffness based on the geometry of the spring whose results could be compared with experimental measurement. The equations are suitable and effective for determining the torsional constant. Several experimental variables existed and, faced with error values presented, it was possible to note the need to keep them in a more controlled future in order to bring the analytical results even closer to the experimental results.
Monografia
Keywords: Molas Helicoidais; Câmbio CVT; Baja; Comet 780; ENGENHARIAS::ENGENHARIA MECANICA